Young people's situated capacity to imagine a desired post-pandemic future: A qualitative methodology for assessing futures consciousness. (December 2022) - Sools, Anneke; Groot, Isolde de; Coppers, Jacqueline; Triliva, Sofia
Abstract: Futures consciousness (FC), considered to be the basis for human anticipation, is important for its role in facing uncertainties and delineating alternative courses of action. This is especially so for emerging adults, who are traversing a life stage fraught with uncertainty and complexity. The COVID-19 pandemic as a high-impact event may trigger modes of engaging with the future to become more explicit. Through critical engagement with the 5-dimensional FC model (Ahvenharju, Minkkinen, & Lalot, 2018), we develop a methodology for qualitatively assessing FC. We analyze how emerging Dutch and Greek adults narrate FC dimensions (time perspective, agency beliefs, openness to alternatives, systemic awareness, concern for others) in letters written from the perspective of a desired post-Corona future. Results show that emerging adults, although caught-up in a subjective timeframe in which the pandemic is enduring, think beyond immediate concerns. They do so in a way that conveys some attribution of agency and systemic awareness. Openness to alternatives is shown using several sophisticated linguistic devices. When further developed, the methodology will enable educators and futurists to support individual's imagination of possible and preferred futures. This may contribute to resilient people and societies in and beyond times of economic, health, and environmental crises. Highlights: Proposes a novel, qualitative methodology for eliciting and analysing futures consciousness based on Letters from the Future. Considers Futures Consciousness as a situated, sense-making capacity. Based on a unique international study on emerging adult's imaginations of a desired post-covid19 future. Captures individual variation and patterns in how the five dimensions of Futures Consciousness are used.